2016
DOI: 10.1016/j.taap.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Application of small RNA sequencing to identify microRNAs in acute kidney injury and fibrosis

Abstract: Establishing a microRNA (miRNA) expression profile in affected tissues provides an important foundation for the discovery of miRNAs involved in the development or progression of pathologic conditions. We conducted small RNA sequencing to generate a temporal profile of miRNA expression in the kidneys using a mouse model of folic acid-induced (250 mg/kg i.p.) kidney injury and fibrosis. From the 103 miRNAs that were differentially expressed over the time course (>2-fold, p<0.05), we chose to further investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…Small RNA sequencing revealed miR-15, miR-383-5p and miR-146b-5p as top upregulated candidates. Interestingly, miR-15 is described to play a role in apoptosis by targeting Bcl2 in chronic lymphocytic leukemia (CLL) 32 and mir-146b-5p was found to be induced in AKI and fibrosis 33 . Top downregulated small RNA candidates in our sequencing analysis were Gm24706, miR-7046-3p and miR-203-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Small RNA sequencing revealed miR-15, miR-383-5p and miR-146b-5p as top upregulated candidates. Interestingly, miR-15 is described to play a role in apoptosis by targeting Bcl2 in chronic lymphocytic leukemia (CLL) 32 and mir-146b-5p was found to be induced in AKI and fibrosis 33 . Top downregulated small RNA candidates in our sequencing analysis were Gm24706, miR-7046-3p and miR-203-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Several rodent studies have demonstrated that drug-induced kidney injury is associated with increased expression of p53-responsive miR-34a, and this miRNA has been shown to suppress autophagy in tubular epithelial cells in a mouse model of ischemia/reperfusion-induced acute kidney injury [ 40 , 41 , 42 , 43 ]. The expression of miR-146-5p was shown to be increased with fibrosis in a mouse model of folic-acid-induced kidney injury, and in mouse models of ischemia/reperfusion injury and unilateral urethral obstruction-induced fibrosis [ 44 ]. Additionally, miR-146-5p expression was increased in human renal cortices with documented severe kidney injury or fibrosis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, some efforts have been initiated through temporal miRNA sequencing experiments following AKI to identify miRNAs that are elevated during periods of repair. Our lab recently conducted small RNA sequencing in mice subjected to folic acid-induced nephropathy and identified 108 miRNAs that were differentially regulated across seven time points[129]. Using principal component analysis, we found that there were unique expression patterns of miRNAs in the injury phase versus the repair and fibrotic phases.…”
Section: Mirnas In Kidney Injury and Repairmentioning
confidence: 99%